2013
DOI: 10.1080/14733145.2013.768287
|View full text |Cite
|
Sign up to set email alerts
|

The path towards a professional identity: An IPA study of Greek family therapy trainees

Abstract: Objective: Contemporary psychotherapy research has focused mainly on practitioners' training and education. The impact of training on professional development and the application of therapeutic skills have been the primary foci of the empirical literature. The aim of this paper is to present the experiences of seven family therapy trainees regarding their personal paths toward the development of professional identity as they underwent training in systemic psychotherapy. Method: In-depth interviews were conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Although most participants linked external support and relational connection to resilience, Jane appeared to place emphasis on self‐reliance. This adds a new dimension to Fragkiadaki et al () as, rather than being nurtured in an accepting and nonjudging training community, Jane suggests her self‐acceptance was born of life's challenges and prior to her training.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Although most participants linked external support and relational connection to resilience, Jane appeared to place emphasis on self‐reliance. This adds a new dimension to Fragkiadaki et al () as, rather than being nurtured in an accepting and nonjudging training community, Jane suggests her self‐acceptance was born of life's challenges and prior to her training.…”
Section: Discussionmentioning
confidence: 94%
“…Through accepting their limitations and weaknesses as beginning therapists, trainees in Fragkiadaki et al () found new, less‐punitive ways of approaching themselves. Moreover, their anxieties were eased through forming more realistic expectations for themselves as therapists.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studying contemporary counselling education can contribute to this enquiry (e.g. Fragkiadaki et al, 2013;Georgiadou, 2014). In a detailed qualitative study of a single counselling student's experience, Folkes-Skinner et al (2010) foregrounded the deconstruction of the counsellor's self.…”
Section: British Counselling Studentsmentioning
confidence: 99%